Ursodeoxycholic Acid Attenuates Endoplasmic Reticulum Stress-Related Retinal Pericyte Loss in Streptozotocin-Induced Diabetic Mice. (3rd January 2017) - Chung, Yoo-Ri; Choi, Jeong A.; Koh, Jae-Young; Yoon, Young Hee
Abstract : Loss of pericytes, an early hallmark of diabetic retinopathy (DR), results in breakdown of the blood-retinal barrier. Endoplasmic reticulum (ER) stress may be involved in this process. The purpose of this study was to examine the effects of ursodeoxycholic acid (UDCA), a known ameliorator of ER stress, on pericyte loss in DR of streptozotocin- (STZ-) induced diabetic mice. To assess the extent of DR, the integrity of retinal vessels and density of retinal capillaries in STZ-induced diabetic mice were evaluated. Additionally, induction of ER stress and the unfolded protein response (UPR) were assessed in diabetic mice and human retinal pericytes exposed to advanced glycation end products (AGE) or modified low-density lipoprotein (mLDL). Fluorescein dye leakage during angiography and retinal capillary density were improved in UDCA-treated diabetic mice, compared to the nontreated diabetic group. Among the UPR markers, those involved in the protein kinase-like ER kinase (PERK) pathway were increased, while UDCA attenuated UPR in STZ-induced diabetic mice as well as AGE- or mLDL-exposed retinal pericytes in culture. Consequently, vascular integrity was improved and pericyte loss reduced in the retina of STZ-induced diabetic mice. Our findings suggest that UDCA might be effective in protecting against DR.